Hubungan Pelaksanaan Praktik Kerja Industri (Prakerin) terhadap Kesiapan Memasuki Dunia Kerja bagi Siswa Kelas XI Kompetensi Keahlian Teknik Kendaraan Ringan SMK Negeri 2 Lubuk Basung - Amal, Nurul; Martias, Martias; Putra, Dwi Sudarno (MSI Transaction on Education, 2020)
This research is based on at least graduates who are accepted to work in the business world or industrial world. The population in this study are students of class XI competence of Light Vehicle Engineering expertise amounted to 81 people and 5 teachers of mentors. Sampling technique is sample random sampling. The sample of this study amounted to 45 students and all mentoring teachers were 5 people. The data collection tool is a validated questionnaire. The results showed that industry work practices were positively and significantly related to the readiness to enter the workforce with a correlation value of 0.227 and a significance value of 0.046. This means that partially industrial work practices have a significant relationship to the readiness to enter the workforce of students of class XI competence in the expertise of Light Vehicle Engineering SMK Negeri 2 Lubuk Basung.